Post‐ischemic salubrinal treatment results in a neuroprotective role in global cerebral ischemia. Issue 2 (16th May 2016) - Anuncibay‐Soto, Berta; Pérez‐Rodríguez, Diego; Santos‐Galdiano, María; Font, Enrique; Regueiro‐Purriños, Marta; Fernández‐López, Arsenio
Abstract: This study describes the neuroprotective effect of treatment with salubrinal 1 and 24 h following 15 min of ischemia in a two‐vessel occlusion model of global cerebral ischemia. The purpose of this study was to determine if salubrinal, an enhancer of the unfolded protein response, reduces the neural damage modulating the inflammatory response. The study was performed in CA1 and CA3 hippocampal areas as well as in the cerebral cortex whose different vulnerability to ischemic damage is widely described. Characterization of proteins was made by western blot, immunofluorescence, and ELISA, whereas mRNA levels were measured by Quantitative PCR. The salubrinal treatment decreased the cell demise in CA1 at 7 days as well as the levels of matrix metalloprotease 9 (MMP‐9) in CA1 and cerebral cortex at 48 h and ICAM‐1 and VCAM‐1 cell adhesion molecules. However, increases in tumor necrosis factor α and nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB) inflammatory markers were observed at 24 h. Glial fibrillary acidic protein levels were not modified by salubrinal treatment in CA1 and cerebral cortex. We describe a neuroprotective effect of the post‐ischemic treatment with salubrinal, measured as a decrease both in CA1 cell demise and in the blood–brain barrier impairment. We hypothesize that the ability of salubrinal to counteract the CA1 cell demise is because of a reduced ability of this structure to elicit unfolded protein response which would account for its greater ischemic vulnerability. Data of both treated and non‐treated animals suggest that the neurovascular unit present a structure‐dependent response to ischemia and a different course time for CA1/cerebral cortex compared with CA3. Finally, our study reveals a high responsiveness of endothelial cells to salubrinal in contrast to the limited responsiveness of astrocytes. The alleviation of ER stress by enhancing UPR with salubrinal treatment reduces the ischemic damage. This effect varies across the different neurovascular unit cell types. The salubrinal neuroprotective effect on CA1 supports differences in neurovascular unit for different brain regions and involves the inflammatory response and its time course. Thus, UPR modulation could be a therapeutic target in cerebral ischemia. Abstract : The alleviation of ER stress by enhancing UPR with salubrinal treatment reduces the ischemic damage. This effect varies across the different neurovascular unit cell types. The salubrinal neuroprotective effect on CA1 supports differences in neurovascular unit for different brain regions and involves the inflammatory response and its time course. Thus, UPR modulation could be a therapeutic target in cerebral ischemia.